Acute corneal hydrops with iatrogenic keratoconus 20 years after radial keratotomy. Issue 2 (1st April 2021) - Gill, Hannah; Shew, William; McGhee, Charles; Crawford, Alexandra
Abstract : A 51-year-old man presented with a history of cloudy vision in the left eye with minimal discomfort. On slitlamp examination, he had 4 well-healed radial keratotomy (RK) incisions in each eye. Severe corneal edema was observed in the inferotemporal aspect of the left eye, consistent with acute hydrops. The patient was managed conservatively with observation and frequent topical lubrication for comfort. The clinical signs of corneal edema resolved over a period of several months, with worsened resultant scarring around the 5-o'clock keratotomy incision. Corneal ectasia is an established late complication of RK. Of interest in this case, the area of corneal hydrops was well demarcated because the RK scars formed a barrier against further progression of corneal edema.